Community and gen Z participation in the party democracy election 2024 towards Indonesia G2G good government to good governance - Saepudin, Eli Apud; Zulfikar, Meiby; Suryasuciramdan, Arfian; Kamilah, Fithrotul (The International Journal of Politics and Sociology Research, 2023)
It is now December 2023 that the Indonesian people will hold general elections for candidates for DPRD members, DPR-RI, DPD-RI, presidential and vice presidential candidates. It is approaching the 2024 election in less than 75 days that the Indonesian people will hold a democratic party to vote directly honestly fair transparently in determining the future of the nation and state of Indonesia for the next five years where the current election participants are dominated by gen z and permanent voters, people are now digitally aware where before voting they see the digital track record of legislative and judicial executive candidates where is their contribution to the nation and state love for the homeland love for the Indonesian people so that the community and gen z do not hesitate not hesitate in choosing candidates for DPRD, DPR-RI, DPD-RI, Presidential and Vice Presidential Candidates for Indonesia five years to come period 2024-2029. The research that the author uses research with qualitative descriptive methods to analyze phenomena, events, or social conditions. The results obtained from this research are how the community is objective and selective in the democratic party of the general election of 14 February 2024.